Solid fuel use, socioeconomic indicators and risk of cardiovascular diseases and all-cause mortality: a prospective cohort study in a rural area of Sichuan, China. (18th September 2021) - Qiu, Shuyi; Chen, Xiaofang; Chen, Xiaofang; Luo, Guojin; Guo, Yu; Bian, Zheng; Li, Liming; Chen, Zhengming; Wu, Xianping; Ji, John S
Abstract: Background: Estimates indicate that household air pollution caused by solid fuel burning accounted for about 1.03 million premature mortalities in China in 2016. In the country's rural areas, more than half the population still relies on biomass fuels and coals for cooking and heating. Understanding the health impact of indoor air pollution and socioeconomic indicators is essential for the country to improve its developmental targets. We aimed to describe demographic and socioeconomic characteristics associated with solid fuel users in a rural area in China. We also estimated the risk of cardiovascular disease and all-cause mortality in association with solid fuel use and described the relationship between solid fuel use, socioeconomic status and mortality. We also measured the risk of long-term use, and the effect of ameliorative action, on mortality caused by cardiovascular disease and other causes. Methods: We used the China Kadoorie Biobank (CKB) site in Pengzhou, Sichuan, China. We followed a cohort of 55 687 people over 2004–13. We calculated the mean and standard deviation among subgroups classified by fuel use types: gas, coal, wood and electricity (central heating additionally for heating). We tested the mediation effect using the stepwise method and Sobel test. We used Cox proportional models to estimate the risk of incidences of cardiovascular disease and mortality with survival days as the time scale, adjusted for age, gender, socioeconomic status, physical measurements, lifestyle, stove ventilation and fuel type used for other purposes. The survival days were defined as the follow-up days from the baseline survey till the date of death or 31 December 2013 if right-censored. We also calculated the absolute mortality rate difference (ARD) between the exposure group and the reference group. Results: The study population had an average age of 51.0, and 61.9% of the individuals were female; 64.8% participants ( n  = 35 543) cooked regularly and 25.4% participants ( n  = 13 921) needed winter heating. With clean fuel users as the reference group, participant households that used solid fuel for cooking or heating both had a higher risk of all-cause mortality: hazard ratio (HR) for: cooking, 1.11 [95% confidence interval (CI) 1.02, 1.26]; heating, 1.34 (95% CI 1.16, 1.54). Solid fuel used for winter heating was associated with a higher risk of mortality caused by cerebrovascular disease: HR 1.64 (95% CI 1.12, 2.40); stroke: HR 1.70 (95% CI 1.13, 2.56); and cardiovascular disease: HR 1.49 (95% CI 1.10, 2.02). Low income and poor education level had a significant correlation with solid fuel used for cooking: odds ratio (OR) for income: 2.27 (95% CI 2.14, 2.41); education: 2.34 (95% CI 2.18, 2.53); and for heating: income: 2.69 (95% CI 2.46, 2.97); education: 2.05 (95% CI 1.88, 2.26), which may be potential mediators bridging the effects of socioeconomic status factors on cardiovascular disease and all-cause mortality. Solid fuel used for cooking and heating accounted for 42.4% and 81.1% of the effect of poor education and 55.2% and 76.0% of the effect of low income on all-cause mortality, respectively. The risk of all-cause mortality could be ameliorated by stopping regularly cooking and heating using solid fuel or switching from solid fuel to clean fuels: HR for cooking: 0.90 (95% CI 0.84, 0.96); heating: 0.76 (95% CI 0.64, 0.92). Conclusions: Our study reinforces the evidence of an association between solid fuel use and risk of cardiovascular disease and all-cause mortality. We also assessed the effect of socioeconomic status as the potential mediator on mortality. As solid fuel use was a major contributor in the effect of socioeconomic status on cardiovascular disease and all-cause mortality, policies to improve access to clean fuels could reduce morbidity and mortality related to poor education and low income.